2022
DOI: 10.1108/mi-09-2022-0162
|View full text |Cite
|
Sign up to set email alerts
|

A novel S-shaped frequency and pattern reconfigurable patch antenna for 4G LTE, WLAN/Wi-Max application

Abstract: Purpose In wireless communication system, use of multiple antennas for different requirements of system will increase the system complexity. However, reconfigurable antenna is maximizing the connectivity to cover different wireless services that operate different frequency range. Pattern reconfigurable antenna can improve security, avoid noise and save energy. Due to their compactness and better performance at different applications, reconfigurable antennas are very popular among the researchers. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Two meandered slots and one monopole fed by three PIN diode's network are used and achieved pattern reconfigurable antenna 7 . Four wire patches on same ground are designed, and SP4T switch is used for beam steering in Santamaria et al 8 ; electromagnetic band gap structure is used to achieve reconfigurability in Faizal Ismail et al 9 Azimuth pattern reconfigurability is achieved using single‐pole three‐throw switching network in Prakash et al 10 Pattern reconfigurability is achieved using three S‐shaped patches with three PIN diodes in Rawal and Rawat 11 . Authors found many literatures for pattern reconfigurable antenna at lower microwave frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Two meandered slots and one monopole fed by three PIN diode's network are used and achieved pattern reconfigurable antenna 7 . Four wire patches on same ground are designed, and SP4T switch is used for beam steering in Santamaria et al 8 ; electromagnetic band gap structure is used to achieve reconfigurability in Faizal Ismail et al 9 Azimuth pattern reconfigurability is achieved using single‐pole three‐throw switching network in Prakash et al 10 Pattern reconfigurability is achieved using three S‐shaped patches with three PIN diodes in Rawal and Rawat 11 . Authors found many literatures for pattern reconfigurable antenna at lower microwave frequencies.…”
Section: Introductionmentioning
confidence: 99%